Airfusion: a machine learning framework for balancing air traffic demand and airspace capacity through dynamic airspace sectorization - Zhou, Wei (2023)
Balancing air traffic demand and airspace capacity is a key challenge in airspace management. This task requires situational awareness among air traffic controllers, necessitating the use of interpretable traffic forecasts and visual tools to facilitate well-informed decision-making processes.